Inhibitory Effect of Cinnamon and Thyme Essential Oils Against Acinetobacter baumannii strains Isolated from Raw Milk and Some Milk Products - Mahmoud Hafouda (South Valley University, 2021)
A total of 250 random samples including raw milk samples collected from street vendors, dairy shops and dairy houses in addition to some milk products including Kariesh cheese, Domiati cheese, cream, and milk powder, were collected from different areas in Luxor city, Egypt. for detection of Acinetobacter species by conventional method and PCR for the presence of blaox51 like gene. results revealed that the 10% of Acinetobacter spp. were recovered from whole raw milk samples, species were A. baumannii, A. calcoaceticus and A. haemolyticus with percentages of 5.3, 2.7 and 2%, respectively. street vendors raw milk samples showed the highest prevalence (14%) of Acinetobacter spp. Regarding milk products samples, 8% of Acinetobacter spp. were isolated from kariesh cheese. A higher percentage of 25% were recorded from cream samples. All Acinetobacter baumanni strains harbored blaox-51 like gene, showing strong lipolytic activity on tributyrin agar, the antibacterial effect of cinnamon oil and thyme oil against 16 Acinetobacter baumanni isolates showed high antibacterial activity.